False flag - Delaborde, Jonas 1981-; Delaborde, Jonas 1981-; Hegray, Hendrik 1981-; Hegray, Hendrik 1981-; Ferraro, James 1986-; Eronen, Roope 1982-; Marquis, Antoine 1974-; Tyfus, Dennis 1979-; Beatty, Robert 1981-; Johnson, Terry; Bomba, Massimiliano 1980-; C. F. 1979-; et al. (F.L.T.M.S.T.P.C, 2010)
False Flag consists of pencil drawings, paintings of domestic scenes seemingly inspired by the late 1950s, early 1960s aesthetic, Sharpie designs and drawings collaged with various textures, experimentation with scanning/photocopying and photography. Black and white images of dated pop culture screen shots and collages of people in riot gear recur throughout. The only attribution of the artists' work in the zine is a scanned list of names. Also included is a colorful, staple-bound red, pink, white and black book made up of predominantly pornographic cartoons
Laserdruck(?) - Zählung ermittelt
Keywords: Graphzine